Genome‐wide association reveals the locus responsible for four‐horned ruminant. (14th January 2016) - Kijas, James W.; Hadfield, Tracy; Naval Sanchez, Marina; Cockett, Noelle
Summary: Phenotypic variability in horn characteristics, such as their size, number and shape, offers the opportunity to elucidate the molecular basis of horn development. The objective of this study was to map the genetic determinant controlling the production of four horns in two breeds, Jacob sheep and Navajo‐Churro, and examine whether an eyelid abnormality occurring in the same populations is related. Genome‐wide association mapping was performed using 125 animals from the two breeds that contain two‐ and four‐horned individuals. A case–control design analysis of 570 712 SNPs genotyped with the ovine HD SNP Beadchip revealed a strong association signal on sheep chromosome 2. The 10 most strongly associated SNPs were all located in a region spanning Mb positions 131.9–132.6, indicating the genetic architecture underpinning the production of four horns is likely to involve a single gene. The closest genes to the most strongly associated marker ( OAR2_132568092 ) were MTX2 and the HOXD cluster, located approximately 93 Kb and 251 Kb upstream respectively. The occurrence of an eyelid malformation across both breeds was restricted to polled animals and those carrying more than two horns. This suggests the eyelid abnormality may be associated with departures from the normal developmental production of two‐horned animals and that the two conditions are developmentally linked. This study demonstrated the presence of separate loci responsible for the polled and four‐horned phenotypes in sheep and advanced our understanding of the complexity that underpins horn morphology in ruminants.